Balancing Track: The Influence of Work-Life Balance, Motivation, Communication, and Work Stress on Job Satisfaction of Jabodebek LRT Drivers - Khoir Sanjaya Siregar; Yuli Kartika Dewi; Rhema Angela Krisandy (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Job satisfaction is an important component of organizational behavior, especially in high-responsibility professions such as rail transportation, where safety, precision, and performance are essential. This study aims to analyze the influence of work-life balance, motivation, communication, and Work Stress on the job satisfaction of train drivers operating the Jabodebek Indonesia Light Rail Transit (LRT). A quantitative research approach was used, involving 100 Jabodebek LRT drivers who were still active as respondents. Data was collected through a structured online questionnaire and analyzed using multiple linear regression with JASP software to determine the relationships between variables. The results of the study show that work-life balance and motivation have a positive and significant effect on job satisfaction. Work Stress also shows a positive and significant influence on job satisfaction, while communication has no significant effect on job satisfaction. Simultaneously, all independent variables were able to explain 81.6% of the variation in job satisfaction. These findings affirm the importance of managing work-life balance, increasing motivation, and managing work stress in an effort to increase job satisfaction of Jabodebek LRT drivers. These findings underscore the importance of implementing integrated managerial strategies, such as flexible work scheduling, strengthening employee motivation systems, improving internal communication channels, and developing effective stress management programs. This effort is critical to improving employee welfare, maintaining optimal performance, and supporting the sustainability of organizational operations in Indonesia's rapidly growing urban rail transportation sector.